Penyuluhan Kepada Masyarakat Tentang Mencuci Tangan Menggunakan Air Bersih Dan Sabun Di SDN Bueng Cala Aceh Besar - Urip Pratama; Rachma Tsanya; Maulid Hidayatun; Virah Matina; Hendina Ade Miranda; Mirna Sofriani; Chilviana Putri; Nur Afri Liandi; Alfidanur Muli; Wulan Karina; Mirda Indriani; Sri Wahyuni (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Health behavior problems in school-aged children are related to the surrounding environment and the individual. One of the main polemics is about personal hygiene, in this case it is about washing your hands using clean water and soap. The aim of this counseling is to determine the knowledge of class VI students at SDN Bueng Cala Aceh Besar, Aceh. This type of counseling uses the method of giving leaflets, pretest, demonstration of 6 steps for washing hands using clean water and soap and posttest in the form of questions and answers. The results of the counseling showed that there was a significant improvement in the majority of class VI students at SDN Bueng Cala after being given hand washing education using clean water and soap.